2001
DOI: 10.1021/ic010263+
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Crystal Structure, and Properties of Barium Pernitride, BaN2

Abstract: Stoichiometric barium pernitride, BaN(2), was prepared from the elements under N(2) pressure of 5600 bar in an autoclave at 920 K. The compound is isotypic to ThC(2) (space group C2/c, Z = 4) according to powder X-ray (neutron) diffraction data with a = 7.1712(1), b = 4.3946(1), c = 7.2362(1) A, and beta = 104.864(1) degrees (a = 7.1745(1), b = 4.3963(1), c = 7.2393(1) A, beta = 104.876(1) degrees ). The N-N distance of 1.221(4) A (based on the neutron diffraction data) is indicative of a double bond in the N(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
87
0
12

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 26 publications
8
87
0
12
Order By: Relevance
“…Magnetic susceptibility measurements and electronic structure calculations for BaN 2 already revealed that the compound exhibits Pauli paramagnetism and should be metallic, despite the paramagnetic triplet state of the diazenide ion. 11 Therefore, a test spin-polarized calculation with nonzero magnetic moments artificially placed on the nitrogen atoms of CaN 2 and SrN 2 was performed and converged also back to the metallic state. Both alkaline earth diazenides crystallize in the same structure type, which is isotypic with the corresponding alkaline earth acetylenides (M AE C 2 ), namely, in a tetragonally distorted NaCl-type.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Magnetic susceptibility measurements and electronic structure calculations for BaN 2 already revealed that the compound exhibits Pauli paramagnetism and should be metallic, despite the paramagnetic triplet state of the diazenide ion. 11 Therefore, a test spin-polarized calculation with nonzero magnetic moments artificially placed on the nitrogen atoms of CaN 2 and SrN 2 was performed and converged also back to the metallic state. Both alkaline earth diazenides crystallize in the same structure type, which is isotypic with the corresponding alkaline earth acetylenides (M AE C 2 ), namely, in a tetragonally distorted NaCl-type.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In a1 922 contribution, Franklin mentioned [15] the doubly deprotonated guanidinate unit [C(NH) 3 ] 2À but without convincing evidence,i np articular without spectroscopic or structural proof.W eh ave finally succeeded in quantitatively synthesizing such an anion in the alkaline-earth metal guanidinate SrC(NH) 3 and determining its crystal structure. Thes tructure was approximately solved, despite the strong scattering power of Sr, from X-ray powder data, significantly improved by DFT calculations,and finally validated by means of highly resolved neutron diffraction ( Figure 1).…”
mentioning
confidence: 99%
“…) in Festkörpern [4] oder Metallkomplexen [5] oder auch der konjugierten Säure H 2 N 2 (Diazen, "Diimin") in Koordinationsverbindungen [6] wurden mit großem Interesse registriert. [7] Der nächste Schritt zum Drei-Elektronen-reduzierten N 2 C 3À (Dinitrid(3À)) wurde bislang nicht intensiv diskutiert, wohl wegen der hohen negativen Ladung zusätzlich zum Radikalcharakter.…”
Section: àunclassified